Mensuração do efeito do novo Código Florestal (Lei 12.651 de 2012) para a evolução do desmatamento nos municípios do estado de Mato Grosso - Prado, Maycon Rodrigues do (2021)
Institutional innovations occur when social actors envision new ways of doing their actions, and this new way of doing things contains an expectation of greater gains. In this context, the new forest law, law n°. 12,651 of May 25, 2012 was an institutional innovation, as it provided new ways to combat deforestation and recover deforested areas, through CAR - Rural Environmental Registry, PRA - Program of Environmental Compliance and CRA – Environmental Reserve Quotas. Therefore, the present work aims to estimate the effect of the promulgation of the new forest code on deforestation in Mato Grosso county in the period 2012-2017. Mato Grosso stands out from the rest of the Brazilian states for the high rate of deforestation in its forests and for being the only state with three biomes in its territory, the Pantanal, Cerrado and Amazon. As a theoretical basis, this work used the studies of the institutional school, present at NIE - New Institutional Economics, to analyze the forest code to deforestation as a process of normative innovation. The methodological procedure used was panel data with fixed effects and the years analyzed were from 2009 to 2017. In order to capture the impact of the forest law on deforestation, a dummy related to the period of validity of the legislation was used. To validate the fixed effect results, the Breush-Pagan and Hausman LM tests were performed, in addition to the multicollinearity tests, by variance factor and the Wald heteroscedasticity test. The results point to the validation of the tests, indicating panel data with fixed effects as the most suitable regression. The variables with statistical significance and with a negative impact on deforestation were command and control through the application of infractions. On the other hand, the variables analyzed that showed statistical significance and a positive relationship for the increase in deforestation were the forest law dummy, expenditure on environmental management, soy planting areas, pasture areas, vegetal extraction and indigenous land. With 99% of statistical significance, institutional innovation, forest code, had a positive effect on the increase in deforestation, between the years 2013 to 2017, in Mato Grosso's county.